2006
DOI: 10.1590/s0004-282x2006000500032
|View full text |Cite
|
Sign up to set email alerts
|

Central auditory evaluation in multiple sclerosis: case report

Abstract: -Herein, we report a case of multiple sclerosis in which peripheral and central hearing, were evaluated through early (brainstem), middle and late auditory evoked potentials before and after corticosteroid therapy. Auditory evaluation revealed better performance on all post-treatment tests. In this case, central auditory function tests (behavioral and electrophysiological) identified the location of the impairment (brainstem), which was in agreement with the patient complaint. The speech in noise test and brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
(9 reference statements)
1
7
0
2
Order By: Relevance
“…The findings of this research have been confirmed and described in studies Schochat et al (23), Magnano et al (19), Gonzáles-Rosa et al (24), Matas et al (25). Magnano et al (19) showed that P300 latencies were significantly increased more than 2 S.D.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of this research have been confirmed and described in studies Schochat et al (23), Magnano et al (19), Gonzáles-Rosa et al (24), Matas et al (25). Magnano et al (19) showed that P300 latencies were significantly increased more than 2 S.D.…”
Section: Discussionsupporting
confidence: 89%
“…In relation to ADHD, many studies have already associated it to alterations in Auditory Processing (AP) (9)(10)(11)(12)(13)4). According to Chermak et al (14), many ADHD symptoms overlap with symptoms of auditory processing disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological measures such as ABR and P300 are often used to analyze the relationship between auditory processing disorder and ADHD (12,(16)(17)(18). Such studies generally show alterations that are related to the magnitude of responses.…”
Section: Introductionmentioning
confidence: 99%
“…They also reveal the integrity and capacity of the central auditory nervous system (CANS) 11,12 , therefore these tests have been increasingly used in the investigation of the auditory pathway of individuals with stuttering.…”
Section: Introductionmentioning
confidence: 99%